Broadband 110 GHz Multiport Scalar Network Analysis Methodology Using Port Extension Across Multiple VNAs - Löffler, Jens; Breun, Sascha; Weigel, Robert; Fischer, Georg (2024 IEEE Asia-Pacific Microwave Conference (APMC), 2024)
This paper presents a novel methodology that en-ables 8-port scalar network analysis measurements with high magnitude accuracy using two individual commercially available network analyzers with frequency extenders. Compared to a single VNA setup, a maximum absolute linear magnitude error below 0.03 up to 110 GHz is demonstrated. The paper describes the required hardware interconnects, as well as the proposed software and calibration algorithms. The achieved accuracy and dynamic range proves to be suitable for the 8-port characteri-zation of crosstalk in highly dense signal routing environments, such as Tbit/s chip-to-chip interfaces, up to a higher frequency range than commercially availabl

High-Frequency Multiport Vector Network Analysis Methodology Using Port Extension Across Multiple VNAs - Löffler, Jens; Koch, Manuel; Breun, Sascha; Weigel, Robert (2024 54th European Microwave Conference (EuMC), 2024)
This paper presents a novel methodology that enables 8-port vector network analysis measurements with high magnitude and phase accuracy using two individual commercially available network analyzers. A maximum phase error of 0.2 degrees and a magnitude error below 0.4 up to 40 GHz is demonstrated, with a multi-port setup using two Keysight PNA-X VNAs in comparison to a standard 4-port setup. The paper shows the required hardware interconnects, as well as the proposed software and calibration algorithms. The achieved accuracy and dynamic range prove to be suitable for the 8-port characterization of crosstalk in highly dense signal routing environments, such as Tbit/s chip-to-chip interfaces, up to a higher frequency range than commercially available.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Crosstalk; Multiport; S-Parameter; SOLT; VNA